The Effect of Student Adversity Quotient on Mathematics Test Scores Using PISA Questions - Firdiansyah, Adin Lazuardy; Rosikhoh, Dewi (Jambura Journal of Mathematics Education, 2024)
This research aimed to determine the effect of student adversity quotient (AQ) on mathematic test scores of 12th-grade students in Pademawu High School, Pamekasan for geometry material. The questions used in the mathematic tests were PISA questions. The type of research was quasi-experimental research applying a quantitative method, and the populations selected were all students of class XII MIPA, as many as 115 people. By using a purposive sampling technique, the sample members were 90 people. Data was collected using questionnaires and tests. The questionnaire used contained 30 daily events, where each event had 2 questions. The math test contained 2 geometry questions. Furthermore, data collected was analysed using descriptive statistical and simple linear regression analysis. It was obtained that the regression model  Y=24,328+0,373X with Y was math test scores and X was AQ scores. From the model, the result showed that there was a significant positive interaction of AQ on the results of mathematic tests at 12th-grade students in Pademawu High School.